The Influence of Work Motivation on Employee Performance at Pt Interna Kawan Setia Karawang - Noviani, Tania; Kristanto, Yudi; Army, Widya Lelisa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The decline in employee performance at PT Interna Kawan Setia can be caused by several factors. Factors that influence performance include work motivation. Phenomena that occur include decreased employee performance, less supportive work motivation. The objectives of this research are 1. To find out the work motivation found at PT Interna Kawan Setia, 2. To find out employee performance at PT Interna Kawan Setia, 3. To find out whether or not there is an influence of work motivation on employee performance at PT Interna Kawan Setia, this research using quantitative methods with associative techniques was carried out at PT Interna Kawan Setia with a population of 32 employees with data collection techniques using questionnaires. Based on the results of statistical calculations, a correlation coefficient of r = 0.787 and a determination coefficient of R = r is obtained2 = 0.619. Testing the significance of the correlation obtained tcount (6,980 > t table (1,697) on α = 0.05, indicating that the correlation coefficient is significant. Thus, the research hypothesis which states that there is a relationship between work motivation and employee performance can be accepted. This means that better work motivation will be followed by higher employee performance. Meanwhile, the coefficient of determination of 0.619 shows that 61.9% of the variation in employee performance can be explained by variations in work motivation, the remaining 38.1% is determined by other factors outside of work motivation.